Improving growth and productivity of Cordia africana trees using moringa leaf juice in north western Ethiopia - Getachew Kassa; Takle Ferde; Amsalu Nigatu (Cogent Food & Agriculture, 2020)
A study was carried out in Bezawite tree nursery site, Bahir Dar, to evaluate the effect of Moringa stenopetala leaf juices on tree seedling growth and survival rates of Cordia africana at different doses in nursery and field condition. Seven treatments were tested, six treatments plus one control without any input, using a RCBD design with three replications were tested. 25ml and 50 ml of leaf juice were sub ministered at three different epochs, emergency, half nursery life span and 30 days before transplanting. Data on root collar diameter, height, and survival rate were collected every 6 months interval for two years in the field condition. Results showed that moringa extract increased growth and survival rate of Cordia africana in the field. Treatment of 50 ml MLJ at emergency shows good survival rate and growth parameters after two years in the field and there is significant difference among treatments in terms of height and root caller diameter as well as survival rate in the field (127.87 cm, 2.44 cm and 87.75%, respectively). Generally, applying moringa leaf juice on Cordia africana had a positive effect on growth parameters and more generally pronounced in the field condition.